Generation of uniform-sized multicellular tumor spheroids using hydrogel microwells for advanced drug screening. Issue 1 (December 2018) - Lee, Jong; Park, Da; Yang, Letao; Kim, Eun-Joong; Ahrberg, Christian; Lee, Ki-Bum; Chung, Bong
Abstract Even thoughin vitro co-culture tumor spheroid model plays an important role in screening drug candidates, its wide applications are currently limited due to the lack of reliable and high throughput methods for generating well-defined and 3D complex co-culture structures. Herein, we report the development of a hydrogel microwell array to generate uniform-sized multicellular tumor spheroids. Our developed multicellular tumor spheroids are structurally well-defined, robust and can be easily transferred into the widely used 2D culture substrates while maintaining our designed multicellular 3D-sphere structures. Moreover, to develop effective anti-cancer therapeutics we integrated our recently developed gold-graphene hybrid nanomaterial (Au@GO)-based photothermal cancer therapy into a series of multicellular tumor spheroid co-culture system. The multicellular tumor spheroids were harvested onto a two-dimensional (2D) substrate, under preservation of their three-dimensional (3D) structure, to evaluate the photothermal therapy effectiveness of graphene oxide (GO)-wrapped gold nanoparticles (Au@GO). From the model of co-culture spheroids of HeLa/Ovarian cancer and HeLa/human umbilical vein endothelial cell (HUVEC), we observed that Au@GO nanoparticles displayed selectivity towards the fast-dividing HeLa cells, which could not be observed to this extent in 2D cultures. Overall, our developed uniform-sized 3D multicellular tumor spheroid could be a powerful tool for anticancer drug screening applications.